Crack mitigation utilizing enhanced bond of rebars in SFRC. (October 2021) - Chu, S.H.; Kwan, A.K.H.
Abstract: The bond of reinforcing bars in concrete can be enhanced by adopting steel fiber reinforced concrete (SFRC). In this research, cracking mitigation utilizing enhanced bond strength and stiffness in SFRC were analytically evaluated. Two values of secant bond stiffness, one at peak bond stress and the other at half peak bond stress, were determined from previous research and found to be each proportional to the bond strength. Comparison of bond strength and stiffness with these published in literature revealed variations. Lastly, mathematical analysis of the crack width in reinforced concrete member was performed. It was demonstrated that the increases in bond stiffness by up to 70% at a steel fiber volume of 2.0% could alleviate the mean crack width by 23% to 50%. More importantly, the rigorous analysis proved that the crack width is more directly related to the bond stiffness rather than the bond strength, suggesting that the bond stiffness plays a decisive role over the τ b in crack control of FRC. The present research lays a scientific foundation for the development of fiber-rebar reinforced concrete (FRRC).